E-Service Quality Analysis of E-Loyalty: Study of Generations X, Y, and Z Fund Users - Ina Kartika Wati; Ali Mumdin; Heri Ispriyahadi (Jurnal Mantik, 2024)
This research investigates the influence of Electronic Service Quality (E-Service Quality) on the level of user loyalty (E-Loyalty) in the Digital Payment System DANA, with a focus on three user generations: Generation X, Millennials, and Z. Through a framework considering service quality dimensions such as system availability, fulfillment, responsiveness, and compensation, this study aims to provide in-depth insights into how user preferences and expectations vary across each generation, influencing loyalty decisions towards DANA services. The research methodology employs a quantitative confirmatory approach using Smart PLS application, involving 150 DANA app users divided into three generational groups. The analysis results indicate that electronic service quality has a significantly positive influence on loyalty levels in each generation.The main findings suggest that Generation X tends to have a stronger relationship between electronic service quality and loyalty, with the highest path coefficient. Although Generation Z has a lower path coefficient, the relationship remains statistically significant. Limitations of this study include constraints in the number of respondents and the focus on DANA app users. The novelty of this research lies in the comparison made among three generations (Generation X, Millennials, and Z) in the context of digital payment services, while another novelty is the detailed assessment of electronic service quality dimensions, such as system availability, fulfillment, responsiveness, and compensation, which significantly shape customer perceptions and loyalty